Legal Products and Political Configuration in Post-Amendment Indonesia: Narratives, Actors, and the Influence of the Digital Society - Wahdini, Muhammad; Habibi, Ahmad; Shaleh, Muhammad Noor (Contemporary Society and Politics Journal, 2025)
This research discusses the dynamic relationship between political configuration, the character of legal products, and the role of the digital society in Indonesian legal politics post the Fourth Amendment of the 1945 Constitution of the Republic of Indonesia. Two classical views on the relationship between law and politics, between law as a social controller and law as a product of societal dynamics, serve as a foundation for understanding contemporary realities. Mahfud MD's findings on the relationship between political configuration and the character of legal products indicate that political changes have direct consequences on the orientation of the regulations that emerge. However, this study highlights that the current political configuration is no longer solely determined by elites and formal structures, but also by a new force: the digital society. The emergence of actors such as influencers, online activists, and political buzzers marks a shift in the way the public participates and influences the course of legislation. On the other hand, the open digital space also presents threats in the form of polarization, disinformation, and digital oligarchy. Through a qualitative approach and literature study, this research finds that Indonesia's legal politics today are becoming increasingly complex, full of challenges, but also hold new hope for broader and more meaningful public participation. The implications of this study emphasize the importance of adaptive legal reforms, paying attention to digital dynamics, and strengthening media ethics as part of the Indonesian legal political ecosystem that upholds decency.